Remembering and Forgetting in the Age of Technology : Teaching, Learning, and the Science of Memory in a Wired World - Miller, Michelle D., 1968- (Book collections on Project MUSE., 2022)
"Concise, nontechnical explanations of major principles of memory and attention, plus ideas for handling technology use in the classroom"--